A new species of Megaperlodes Yokoyama et al. 1990 (Plecoptera, Perlodidae) from the South of the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2015)
A new species of Plecoptera Megaperlodes tiunovi sp. n., from the South of the Russian Far East is described and illustrated. The relationships with its close relatives are discussed. Newly discovered features are added to the diagnosis of the genus Megaperlodes, especially previously overlooked eversible lobes within the paraprocts, egg structure, and wing venation.